Bahasa Indonesia sebagai Simbol Kesatuan dalam Dinamika Era Globalisasi pada Masyarakat Kamal - M. Azaz Alfian; Ahzu Ainur Rohmah; Elsa Farista; Bima Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The growth of the era of globalization is marked by the rapid flow of information and cultural exchange, this is evidenced by changes in the use of Indonesian by the dominance of the use of foreign languages. The aim of this research is to find out more deeply about Indonesian as a symbol of unity in the dynamics of the era of globalization. This type of research is qualitative with a descriptive approach with data collection techniques using library research. The research results show that Indonesian plays a very important role as a symbol of unity in the era of globalization, especially in the Kamal community. With language education that focuses on preserving authenticity and developing local vocabulary, together with an understanding of the importance of Indonesian as a cultural heritage, can be an effective strategy in maintaining this symbol of unity. Thus, Indonesian is not just a communication tool, but also a solid foundation in building identity and unity amidst the dynamics of the era of globalization.